Acute Mountain Sickness in Physically Active Individuals: The Role of Fitness, Acclimatization and Symptom Monitoring in Preparation for Mountain Exercise - A Narrative Review - Częczek, Kacper; Cieślewicz, Karolina; Braksal, Barbara; Minik, Bartosz; Szymańska- Zdyb, Kinga; Nowaczek, Patrycja; Mirkowski, Krzysztof; Szurek, Zuzanna Wanda; Chyła, Zofia Julia; Miroński, Adam (Quality in Sport, 2026)
Background. Mountain exercise, trekking, skiing and altitude training expose physically active individuals to hypobaric hypoxia and acute altitude illness. AMS usually occurs after rapid ascent above approximately 2500 m and may impair safety and performance. Aim. This narrative review summarizes evidence on AMS in physically active individuals, focusing on fitness, ascent profile, acclimatization, load management, hydration, nutrition, symptom monitoring and anti-doping issues. Material and methods. A PubMed-based narrative search was performed in May 2026 using terms related to AMS, altitude illness, athletes, exercise, mountaineering, acclimatization, prevention, Lake Louise Score, oxygen saturation, hydration and nutrition. English-language studies, reviews, consensus statements and guidelines were prioritized. WADA documents were consulted for doping issues. Results. Rapid ascent, inadequate acclimatization, previous altitude illness, high early exercise intensity, individual oxygenation responses and poor symptom awareness are clinically important determinants of AMS risk. Fluid and energy imbalance may worsen exercise tolerance and complicate symptom interpretation, but they are not substitutes for acclimatization. The 2018 Lake Louise AMS Score is a practical field tool, whereas SpO2 and heart rate are supportive parameters only. Conclusions. High physical fitness does not eliminate AMS risk. Preparation should combine gradual ascent, low training load during the first 24-48 h, individualized risk assessment, adequate nutrition and hydration, and daily symptom monitoring. New headache with gastrointestinal symptoms, dizziness, unusual fatigue, ataxia, confusion or dyspnea at rest should prompt rest, cessation of ascent and, when indicated, descent or treatment.